Information cues and emotional appeals in magazine advertisements - Mücahid Zengin; Güldane Zengin (Vivat Academia)
Introduction: The aim of this study is to reveal how advertising messages were constructed in Turkish magazines, in addition to revealing the state of Turkish magazines in the span of seven years. Methodology: A content analysis has been conducted to reveal the usage levels of information cues and emotional appeals on 876 advertisements published in Turkish magazines in February 2018, 2021, and 2024. Results: Magazines carry a lower number of ads compared to 2018, with some exceptions. Information cues are present in all ads, while emotional appeals are found in 35,3%. There is a statistically significant difference in Price/Value, Quality, Availability, Independent Research, Company Research and New Ideas cues and humor appeal across the years. The most used emotional appeal is the warmth appeal (23,9%), and it is followed by nostalgia (5,8%), eroticism (5,3%), humor (2,5%) and fear (1,9%). Discussion and conclusions: Print magazines are facing challenges in an increasingly digital environment. In addition, the effects of the pandemic are evident in the advertisements published in 2021, according to our findings. However, not all magazines are the same. Some of the magazines have a higher ad-to-total page number ratio compared to 2018. Another factor affecting magazine advertising and advertisers in general is the economic challenges. These are reflected in the use of cues and appeals. Among the emotional appeals, warmth may be relatively low-risk compared to the rest, and this may explain their lower percentages.